Protecting the self : defense mechanisms in action - Cramer, Phebe (Guilford Press, 2006)
Integrating theory, research, and applications, this book examines the defense mechanisms and their role in both normal development and psychopathology. It describes how children and adults mobilize specific kinds of defenses to maintain their psychological equilibrium and preserve self-esteem, particularly in situations of trauma or stress.